TRAIL treatment prevents renal morphological changes and TGF-β-induced mesenchymal transition associated with diabetic nephropathy. Issue 17 (10th September 2020) - Toffoli, Barbara; Tonon, Federica; Tisato, Veronica; Michelli, Andrea; Zauli, Giorgio; Secchiero, Paola; Fabris, Bruno; Bernardi, Stella
Abstract: Background: TNF-related apoptosis-inducing ligand (TRAIL) has attracted attention not only as an anti-cancer agent, but also as a potential treatment for diabetes. Animal studies have shown that TRAIL delivery ameliorated glucose control in type 1 and type 2 diabetes. It is currently unknown whether TRAIL positive effects are maintained in more severe forms of type 2 diabetes, and whether they include renoprotection. Our study aimed at evaluating TRAIL effects in a severe form of type 2 diabetes with nephropathy. Materials and methods: A total of 20 db/db mice were treated with saline or TRAIL twice per week for 12 weeks. In parallel, renal tubular epithelial cells were cultured with TGF-β1 in the presence and absence of TRAIL, with and without silencing TRAIL-specific receptor (DR5) and leptin receptor. Results: TRAIL did not improve glucose control, but it significantly reduced circulating interleukin (IL)-6 and resistin. In the kidney, TRAIL treatment significantly ameliorated glomerular and tubular morphology with an improvement in kidney function, but no effect on proteinuria. Our in vitro studies on TGF-β1-treated cells, showed that by binding to DR5, TRAIL rescued normal tubular cell morphology, increasing E-cadherin and reducing α-smooth muscle actin (SMA) expression, with no effects on cell viability. Interestingly, both in vivo and in vitro, TRAIL reduced the accumulation of the autophagy substrate p62. Conclusions: Our data confirm TRAIL protective effects against organ damage and shed light on to promising anti-fibrotic actions, which are independent of glucose control. TRAIL anti-fibrotic actions might be due to the rescue of autophagy in diabetes.